Oxidative Stress and Risk of Dementia in Older Patients with Depression: A Longitudinal Cohort Study Using Plasma Biomarkers - Yoo-Jin Jang; Min-Ji Kim; Su-Jin Lee; Shinn-Won Lim; Doh-Kwan Kim (Medicina)
Background and Objectives: While depression is associated with an increased risk of Alzheimer’s dementia (AD), traditional AD-related biomarkers, such as amyloid-beta, have shown limited predictive value for late-life depression. Oxidative stress has emerged as a potential indicator given its shared role in both depression and dementia. This study investigated the longitudinal relationship between oxidative stress biomarkers and risk of dementia in patients with depression. Materials and Methods: A longitudinal cohort of 146 older patients with major depressive disorder was analyzed. Biomarkers, such as nitrotyrosine, protein carbonyl, F2-isoprostanes, malondialdehyde, 4-hydroxynonenal, and 8-hydroxy-2′-deoxyguanosine, were collected at baseline and measured using an enzyme-linked immunosorbent assay. AD conversion was determined using comprehensive neuropsychological assessment. Cox proportional hazards models were used to evaluate the association between oxidative stress biomarkers and AD conversion after adjusting for confounders. The log-rank test, using the minimum p-value approach, was applied to determine the optimal cut-off value for significantly associated biomarkers of AD-free survival rates. Results: During the follow-up period ranging from 1.00 to 18.53 years, 41 (28.08%) patients converted to AD. Nitrotyrosine showed a significant association with increased risk of AD (adjusted hazard ratio [HR], 1.01; 95% confidence interval [CI], 1.00–1.01; p = 0.0045). For clinical applicability, patients with plasma nitrotyrosine levels ≥170 nM as the cut-off value had a 5.14-fold increased risk of AD (adjusted HR, 5.14; 95% CI, 2.02–13.07; p = 0.0006). Other biomarkers, such as protein carbonyl, F2-isoprostanes, malondialdehyde, 4-hydroxynonenal, and 8-hydroxy-2′-deoxyguanosine, were not significantly associated with AD conversion. Conclusions: Nitrotyrosine, a biomarker that reflects nitrosative damage, emerged as a significant predictor of dementia risk in older patients with depression, highlighting its potential as an early biomarker of dementia. Further validation of these results is required using a larger sample size.